IDDF2018-ABS-0251 Ductal clearance of calculi delays the development of diabetes in patients with idiopathic chronic pancreatitis. (June 2018) - Talukdar, Rupjyoti; Tandan, Manu; Lakhtakia, Sundeep; Ramchandani, Mohan; Gupta, Rajesh; Pradeep, Rebala
Abstract : Background: In this study, we evaluate the effect of pancreatic ductal clearance on its development in chronic pancreatitis (CP). Methods: Consecutive patients visiting the Pancreas Clinic between 1 st Aug, 2011–31stJul, 2012 were enrolled. Data on demography/disease progression/morphology (imaging)/treatment were recorded after verifying available documents. Thereafter patients were prospectively followed 6-mthly till June 2017. Patients who couldn't return were interviewed telephonically. Patients without complete data and those who lost to follow-up were excluded. Prospective data till June 2017 is presented. Chi-square test was performed for categorical variables; Student's 't' or the Mann Whitney U test was conducted for continuous variables. Binary logistic regression was performed to identify disease-related factors that imparted independent risk of development of diabetes. Kaplan-Meier survival analysis was used to compare the diabetes-free interval since onset of CP symptoms, and Cox-proportional hazards model to calculate the hazard ratio (HR) (95% confidence interval[CI]). Two-tailed 'p' value of <0.05 was considered statistically significant. Results: 644 patients were enrolled, of which 137 were excluded. Of the 507 analysed patients, 312 (61.5%) had idiopathic CP. 283 (55.8%) patients underwent ductal clearance (ESWL/ERCP 232, drainage surgery 27, surgery following ESWL 24). 190 (37.5%) patients developed diabetes. Mean(SD) duration between onset of CP symptoms and ductal clearance was 3.4 (3.2) yrs. Alcohol intake and pancreatic ductal calculi were independently associated with the development of diabetes (OR[95% CI] of 2.01 [1.16–3.47], p=0.03 and 2.04 [1.38–3.01], p<0.0001 respectively). Kaplan-Meier estimate for diabetes free patients was significantly higher in the patients who underwent ductal clearance in patients with idiopathic CP (p=0.001 by Log-rank test), with a Hazard ratio (HR[95% CI]) of 2.01 (1.3–3.0), p=0.002 (figure 1). This was not significantly different for patients with non-idiopathic (alcohol ±smoking) CP. Conclusions: Pancreatic ductal calculi increase the risk of diabetes in CP. Early ductal clearance of stones could prolong the diabetes-free interval in patients with idiopathic CP.